Amyotrophic Lateral Sclerosis: Proteins, Proteostasis, Prions, and Promises - McAlary, Luke; Chew, Yee Lian; Lum, Jeremy Stephen; Geraghty, Nicholas John; Yerbury, Justin John; Cashman, Neil R. (Frontiers in Cellular Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is characterised by the progressive degeneration of the motor neurons that innervate muscle, resulting in gradual paralysis and culminating in the inability to breathe or swallow. This neuronal degeneration occurs in a spatiotemporal manner from a point of onset in the central nervous system, suggesting that there is a molecule that spreads from cell-to-cell. There is strong evidence that the onset and progression of ALS pathology is a consequence of protein misfolding and aggregation. In line with this, a hallmark pathology of ALS is protein deposition and inclusion formation within motor neurons and surrounding glia of the proteins TAR DNA-binding protein 43, superoxide dismutase-1, or fused in sarcoma. Collectively, the observed protein aggregation, in conjunction with the spatiotemporal spread of symptoms, strongly suggests a prion-like propagation of protein aggregation occurs in ALS. In this review, we discuss the role of protein aggregation in ALS in relation to protein homeostasis (proteostasis) mechanisms and prion-like propagation. Furthermore, we examine the experimental models used to investigate these processes, including in vitro assays, cultured cells, invertebrate models, and murine models. Finally, we evaluate the therapeutics that may best prevent onset or spread of pathology in ALS, and discuss what lies on the horizon for treating this currently incurable disease.